Impact of Corticosteroid on Covid-19 Pneumonia Patients - Mishra, Navin Kumar; Karn, Rohit; Shrestha, Milan; Acharya, Abhiskar; Acharya, Sunil; Dahal, Suresh; Neopane, Arpana (Nepalese Respiratory Journal, 2024)
Background: Globally over 704,753890 had COVID -19 Out of which 7,010,681 died compared to 12031 death in Nepal out of1003450 cases Nationwide. Corticosteroids because of their anti- inflammatory effect may have beneficial effect/s on COVID-19 patients. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the pathogen responsible for the coronavirus disease 2019 (COVID-19) pandemic, which has resulted in global healthcare crises and strained health resources. Corticosteroids are a potential therapeutic agent for patients with COVID-19 pneumonia. The RECOVERY (Randomised Trials in COVID-19 Therapy) trial provided data on the mortality benefits of corticosteroids. Aim: The study aims to see the effect of Corticosteroids on COVID-19 patient outcomes concerning disease progression, length of hospital stay, 28-day mortality, and use of resources like Ventilator. Method: Single Hospital-based Prospective observational study among RT-PCR positive for COVID-19 patients admitted at Kathmandu Medical College Teaching Hospital from June 01, 2021 –July 31st, 2021 requiring oxygen therapy. Patients were grouped into either usual care, including symptomatic treatment only, or a group receiving both usual care and Corticosteroid. Results: This study included 160 RT-PCR-positive cases. There were 53 patients with mild symptoms and 107 with moderate symptoms. Patients with mild symptoms who received standard care had an odds ratio of 1.875 for progression to moderate and severe COVID-19 Compared to those who received both standard care and corticosteroid. Similarly, Patients with moderate symptoms who received standard care had an odds ratio of 1.8 for progression to severe and critical COVID-19 Compared to those who received both standard care as well as corticosteroids. Among patients with mild symptoms, the overall use of a ventilator was 35.85 % and mortality was 13.21 %. Similarly, in patients with moderate symptoms at presentation, a ventilator was needed in 33.64 % and mortality was 24.30 %. Conclusion: Though Corticosteroids seem to have a beneficial role in preventing disease progression, they failed to show a statistically significant reduction of ventilator use and mortality benefit amongst groups.